Eosinophilic pneumonia: a case of daptomycin induced lung injury - Vaishnavi Raman; Isha Chaudhary; Sean Shieh (Greater Baltimore Medical Center, 2021)
Eosinophilic pneumonia is a category of lung diseases characterized by an increased number of eosinophils in alveolar spaces and interstitium. Acute cases are often caused by fungal infections, parasites, drugs or toxins and can present with respiratory failure. Daptomycin has been identified as one of the rare causes of acute eosinophilic pneumonia. We describe a case of an elderly man on daptomycin for MRSA endocarditis treatment who presented to the hospital with fevers and dyspnea within two weeks of daptomycin initiation. As an inpatient, he developed an increasing oxygen requirement necessitating intensive care unit management. Daptomycin cessation improved his symptoms and he was placed on a steroid taper. These findings suggested a diagnosis of daptomycin-induced eosinophilic pneumonia. However, the patient deteriorated and eventually passed away despite resuscitative efforts. This case highlights the importance of prompt identification of eosinophilic pneumonia, its potential severity and the need for more exploration regarding the timing of corticosteroid taper. This in turn will inform more effective approaches to this condition in the future.